2023
DOI: 10.1515/cclm-2023-0280
|View full text |Cite
|
Sign up to set email alerts
|

Serum GFAP – pediatric reference interval in a cohort of Danish children

Abstract: Objectives Glial fibrillary acidic protein (GFAP) in blood is an emerging biomarker of brain injury and neurological disease. Its clinical use in children is limited by the lack of a reference interval (RI). Thus, the aim of the present study was to establish an age-dependent continuous RI for serum GFAP in children. Methods Excess serum from routine allergy testing of 391 children, 0.4–17.9 years of age, was measured by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, no physiological reference values have been established to date for children in regards to UCH-L1, and only one recent study has proposed a paediatric reference interval for GFAP, in a cohort of Danish children. 35 As with other brain biomarkers, 36 it has been shown that age can influence their concentrations and that GFAP levels after severe trauma were higher in a paediatric cohort than in adults. 31 The overall aim of the BRAINI-2 paediatric study is to provide new knowledge regarding GFAP and UCH-L1 in children and adolescents in order to improve TBI management in the paediatric population.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%
“…In addition, no physiological reference values have been established to date for children in regards to UCH-L1, and only one recent study has proposed a paediatric reference interval for GFAP, in a cohort of Danish children. 35 As with other brain biomarkers, 36 it has been shown that age can influence their concentrations and that GFAP levels after severe trauma were higher in a paediatric cohort than in adults. 31 The overall aim of the BRAINI-2 paediatric study is to provide new knowledge regarding GFAP and UCH-L1 in children and adolescents in order to improve TBI management in the paediatric population.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%